Median nerve entrapments in the forearm - a case report of rare anterior interosseous nerve syndrome - Vondra, P; Vlach, M (Acta chirurgiae plasticae, 2023)
Nowadays, median nerve entrapment is a frequent issue. Many physicians are familiar with the most common median entrapment, which is the carpal tunnel syndrome (CTS). By contrast, less frequent entrapments, historically called "pronator syndrome" are still misdiagnosed as overuse syndrome, flexor tendinitis or other conditions. This article is meant to introduce proximal median nerve entrapments, followed by a case report of the rarest example - anterior interosseous nerve syndrome (AIN syndrome).
Keywords: Upper Extremity; nerve entrapment; předloktí; Median Neuropathy; horní končetina; mononeuropatie; Mononeuropathies; median nerve; neuropatie nervus medianus; lidé; neurosurgery; Forearm; median neuropathy; Humans; nerve compression syndromes; Carpal Tunnel Syndrome; syndrom karpálního tunelu